Sn-based brazing filler metal capable of achieving high-reliability interconnection of microwave assemblies

By adding Cu NWs, Sn, Ag and Cu to the Sn-based solder to form an alloyed structure, the problem of insufficient performance of existing lead-free solder is solved, the strength and reliability of microwave components are significantly improved, and the demand for high-density and high-integration microwave products is met.

CN119794651APending Publication Date: 2025-04-11YANGZHOU HAIKE ELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510048441.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lead-free soldering system is difficult to meet the traditional Sn-Pb solder in terms of performance, and the solder joint strength and reliability of microwave components are insufficient, making it difficult to meet the needs of high-density and high-integration microwave products.

Method used

Using Sn-based solder, Cu NWs, Sn, Ag and Cu were added, and the mass percentage of each component was: Cu NWs content was 0.05-0.8%, Cu content was 0.5%, Ag content was 1.0%, and the rest was Sn. After stirring and mixing, melting characteristics, wetting tests and shear tests were performed.

Benefits of technology

It significantly improves the strength and reliability of microwave components, enhances wetting and mechanical properties, extends fatigue life, and meets the high reliability requirements of microwave components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794651A_ABST
    Figure CN119794651A_ABST
Patent Text Reader

Abstract

The invention discloses Sn-based brazing filler metal capable of realizing high-reliability interconnection of microwave components, which comprises the Sn-based brazing filler metal, and the Sn-based brazing filler metal comprises the following components in percentage by mass: 0.05-0.8% of Cu NWs, 0.5% of Sn, 1.0% of Ag and the balance of Sn; the method for testing the Sn-based brazing filler metal comprises the following steps that S1, the Sn-based brazing filler metal and the Cu NWs reinforcing phase are mixed, and the stirring time is 30 min; specifically, in the embodiment, the substrate brazing filler metal and the Cu NWs reinforcement phase (the diameter ranges from 100 nm to 200 nm, and the average length is 5 microns) are mixed through a mechanical stirring method, and the stirring time is 30 min. And S2, a melting characteristic test, a wettability test and a shear test are carried out respectively. A melting characteristic test of the composite brazing filler metal is carried out according to the Japanese industrial standard JIS Z3198, a differential thermal analysis (DTA) method is adopted in the melting characteristic test, and the influence of the content of Cu NWs on the melting characteristic of the composite brazing filler metal is measured through a differential scanning calorimeter (DSC).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chip-level packaging, and in particular relates to a Sn-based solder capable of realizing high-reliability interconnection of microwave components. Background Art

[0002] Microwave multi-chip modules (abbreviated as "microwave modules") are component-level composite devices that are composed of a multilayer ceramic substrate sintered in a metal tube shell, and then the passive components such as resistors, inductors and capacitors are electrically connected to the bare chip using a microelectronic interconnection process, and finally hermetically sealed. They are high-density, highly integrated microwave products. Microwave modules have very obvious advantages in increasing assembly density, shortening interconnection length, reducing weight, reducing volume and improving reliability. It is currently the best way to maximize high integration and realize the miniaturization, multi-function and high reliability of microwave signal transceivers. In recent years, microwave module technology has developed rapidly and has been widely used in aerospace, computers, communications and other fields, becoming an indispensable core technology equipment for space applications.

[0003] In the process of microwave assembly, brazing is the main way to interconnect electronic components. In the brazing process, solder joints play a vital role, and the failure of microwave components is often related to the failure of solder joints. On the one hand, solder joints can play a role of mechanical support to prevent external forces from damaging the device; on the other hand, solder joints can play a role of electronic interconnection to ensure the transmission of current and signals. In addition, solder joints can also play a role in heat dissipation, moisture resistance and corrosion resistance to a certain extent. In order to form a good solder joint, a solder with excellent comprehensive performance must be used.

[0004] At present, the main lead-free solder systems include Sn-Bi, Sn-Zn, Sn-Ag, Sn-Ag-Cu and Sn-Cu. However, these lead-free solders have their own advantages and disadvantages, and it is difficult to approach the traditional Sn-Pb solder in terms of performance. Therefore, it is urgent to use the alloying of Sn-Ag-Cu solder to improve the comprehensive performance of the solder and improve the structure of the solder. Summary of the invention

[0005] The purpose of the present invention is to solve the above problems and provide a Sn-based solder which can significantly improve the strength of microwave components and has good wettability, high mechanical properties and high fatigue life and can meet the high reliability requirements of microwave components.

[0006] In order to solve the above technical problems, the technical solution of the present invention is: a Sn-based solder capable of realizing high-reliability interconnection of microwave components, comprising a Sn-based solder, wherein the Sn-based solder components include: Cu NWs, Sn, Ag and Cu, wherein the mass percentage of each component is: Cu NWs content is 0.05-0.8%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn;

[0007] The Sn-based solder testing step comprises the following steps:

[0008] S1, mix the Sn-based solder and Cu NWs reinforcement, stirring time is 30min;

[0009] S2. Carry out melting characteristic test, wettability test and shear test respectively.

[0010] Preferably, the melting characteristic test adopts a differential thermal analysis (DTA) method, and uses a differential scanning calorimeter (DSC) to measure the effect of the Cu NWs content on the melting characteristics of the composite solder.

[0011] Preferably, the melting characteristics test comprises the following sub-steps:

[0012] S11. During the test, high purity argon gas was introduced into the sample chamber to prevent oxidation;

[0013] S12, then put 10 mg of solder sample into an Al2O3 crucible;

[0014] S13. The test temperature range is 30℃~300℃, and the heating rate is set to 10℃ / min. In order to improve the accuracy of the test, three tests are performed for each group.

[0015] Preferably, before the wettability test, first, the copper substrate is cleaned with alcohol in an ultrasonic cleaner for two minutes; then, 0.2±0.01 g of the sample is coated on the copper substrate and heated on a constant temperature hot plate for 30 minutes at a heating temperature of 250°C; after cooling to room temperature, the sample is removed from the constant temperature hot plate; after the sample is cooled, a camera is used to take a picture, and then the spreading area of ​​the solder is measured using ImageJ software; finally, the average spreading area of ​​the composite solder of the same composition is calculated.

[0016] Preferably, before the shear test, a Cu plate with a length of 40 mm, a width of 4 mm and a height of 0.6 mm is manually polished using sandpaper of different particle sizes; then it is immersed in alcohol and ultrasonically cleaned; then the solder and the Cu plate are prepared into samples required for the shear test; finally, the shear test is performed using an electronic universal testing machine model UTM5000.

[0017] Preferably, the Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.05%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

[0018] Preferably, the Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.1%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

[0019] Preferably, the Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.2%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

[0020] Preferably, the Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.4%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

[0021] Preferably, the Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.8%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

[0022] The beneficial effects of the present invention are:

[0023] 1. The Sn-based solder provided by the present invention can realize high-reliability interconnection of microwave components, and the surface tension is reduced, thereby improving the flowability of the liquid solder.

[0024] 2. The Cu NWs of the present invention can serve as pinning points of grain boundaries, inhibiting the growth of grains, thereby significantly refining the microstructure of the solder.

[0025] 3. The Cu NWs of the present invention can inhibit the growth of IMC on the Sn1.0Ag0.5Cu-xCu NWs / Cu interface. The inhibitory effect of Cu NWs on grain growth can be attributed to the adsorption effect of Cu NWs.

[0026] 4. After adding a proper amount of CuNWs in the present invention, the number of dimples in the solder joint fracture increases significantly, showing obvious ductile fracture.

[0027] 5. The present invention can significantly improve the strength of microwave components, and has good wettability, high mechanical properties and high fatigue life, and can meet the high reliability requirements of microwave components. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The invention provides a design, manufacturing and testing step for a Sn-based solder capable of realizing high-reliability interconnection of microwave components;

[0029] Figure 2 It is a melting characteristic diagram of six groups of implementation schemes of the present invention with different Cu NWs contents when other components remain unchanged;

[0030] Figure 3 is a graph of spreading area (wetting performance) of six groups of implementation schemes of the present invention with different Cu NWs contents when other components remain unchanged;

[0031] Figure 4 are microstructure diagrams of six groups of embodiments of the present invention with different Cu NWs contents when other components remain unchanged;

[0032] Figure 5 It is the interface organization diagram of six groups of implementation schemes of the present invention with different Cu NWs contents when other components remain unchanged;

[0033] Figure 6 Graphs showing the shear strength of six groups of embodiments of the present invention with different Cu NWs contents when other components remain unchanged. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments:

[0035] Embodiment 1

[0036] like Figure 1 As shown, the Sn-based solder provided by the present invention can realize high-reliability interconnection of microwave components, including the Sn-based solder, and the Sn-based solder components include: Cu NWs, Sn, Ag and Cu, and the mass percentage of each component is: Cu NWs content is 0.05-0.8%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn. The preparation and analysis steps of the Sn-based solder of the present invention are: first design the composition of the solder alloy, then manually mix and prepare the SnAgCu composite solder, then perform a wetting and spreading test, a melting characteristic test and a mechanical property test, then observe and analyze the matrix and interface structure, and finally perform an analysis of the growth kinetics of the interface IMC during aging and thermal cycling.

[0037] The specific testing steps of Sn-based solder include the following steps:

[0038] S1. Mix the Sn-based solder and the Cu NWs reinforcement phase, and stir for 30 min.

[0039] Specifically, in this embodiment, the base solder and the Cu NWs reinforcement phase (with a diameter between 100 and 200 nm and an average length of 5 μm) were mixed by mechanical stirring for 30 minutes.

[0040] S2. Carry out melting characteristic test, wettability test and shear test respectively.

[0041] The melting characteristics test of the composite solder was carried out according to Japanese Industrial Standard JIS Z3198. The melting characteristics test adopted the differential thermal analysis (DTA) method, and the effect of Cu NWs content on the melting characteristics of the composite solder was measured by differential scanning calorimetry (DSC).

[0042] The melting characteristics test includes the following sub-steps:

[0043] S11. During the test, high purity argon gas was introduced into the sample chamber to prevent oxidation.

[0044] S12. Then put 10 mg of solder sample into the Al2O3 crucible.

[0045] S13. The test temperature range is 30℃~300℃, and the heating rate is set to 10℃ / min. In order to improve the accuracy of the test, three tests are performed for each group.

[0046] Before the wettability test, first, the copper substrate was cleaned with alcohol in an ultrasonic cleaner for two minutes. Then, 0.2±0.01g of the sample was coated on the copper substrate and heated on a constant temperature hot plate for 30min at a heating temperature of 250℃. After cooling to room temperature, the sample was removed from the constant temperature hot plate. After the sample cooled, it was photographed with a camera, and the spreading area of ​​the solder was measured using ImageJ software. Finally, the average spreading area of ​​the composite solder with the same composition was calculated.

[0047] In order to study the microstructure of the composite solder with different contents of CuNWs and the microstructure of the interface IMC, the wettability test specimens were cut along the cross section and then embedded in epoxy resin. Then the following steps were performed: grinding, polishing and etching. Finally, the microstructure of the composite solder and the interface IMC layer were observed by scanning electron microscopy (SEM).

[0048] Before the shear test, the Cu plate with a length of 40 mm, a width of 4 mm and a height of 0.6 mm was manually polished using sandpaper of different particle sizes. Then it was placed in alcohol for immersion and ultrasonic cleaning. Then the solder and the Cu plate were prepared into samples required for the shear test. Finally, the shear test was performed by an electronic universal testing machine with a model of UTM5000. This embodiment is used as a substrate material embodiment.

[0049] Embodiment 2

[0050] Compared with the first embodiment, the present embodiment differs from the first embodiment in that the composition of the Sn-based solder and the mass percentage of each component are preferably: 0.05% Cu NWs content, 0.5% Cu content, 1.0% Ag content, and the rest is Sn. The rest is the same as the first embodiment.

[0051] Embodiment 3

[0052] Compared with the first embodiment, the present embodiment differs in the following aspects: the composition of the Sn-based solder and the mass percentage of each component are preferably: 0.1% Cu NWs content, 0.5% Cu content, 1.0% Ag content, and the rest is Sn. The rest is the same as the first embodiment.

[0053] Embodiment 4

[0054] Compared with the first embodiment, the present embodiment differs in the following aspects: the composition of the Sn-based solder and the mass percentage of each component are preferably: 0.2% Cu NWs content, 0.5% Cu content, 1.0% Ag content, and the rest is Sn. The rest is the same as the first embodiment.

[0055] Embodiment 5

[0056] Compared with the first embodiment, the present embodiment differs in the following aspects: the composition of the Sn-based solder and the mass percentage of each component are preferably: 0.4% Cu NWs content, 0.5% Cu content, 1.0% Ag content, and the rest is Sn. The rest is the same as the first embodiment.

[0057] Embodiment 6

[0058] Compared with the first embodiment, the present embodiment differs in the following aspects: the composition of the Sn-based solder and the mass percentage of each component are preferably: 0.8% Cu NWs content, 0.5% Cu content, 1.0% Ag content, and the rest is Sn. The rest is the same as the first embodiment.

[0059] Those skilled in the art will appreciate that the embodiments described herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.

Claims

1. A Sn-based solder capable of realizing high reliability interconnection of microwave components, characterized in that: The invention comprises a Sn-based solder, wherein the Sn-based solder comprises: Cu NWs, Sn, Ag and Cu, wherein the mass percentage of each component is: the content of Cu NWs is 0.05-0.8%, the content of Cu is 0.5%, the content of Ag is 1.0%, and the rest is Sn; The Sn-based solder testing step comprises the following steps: S1, mix the Sn-based solder and Cu NWs reinforcement, stirring time is 30min; S2. Carry out melting characteristic test, wettability test and shear test respectively.

2. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The melting property test adopts a differential thermal analysis (DTA) method and uses a differential scanning calorimeter (DSC) to measure the effect of the Cu NWs content on the melting property of the composite solder.

3. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The melting characteristics test includes the following steps: S11. During the test, high purity argon gas was introduced into the sample chamber to prevent oxidation; S12, then put 10 mg of solder sample into an Al2O3 crucible; S13. The test temperature range is 30℃~300℃, and the heating rate is set to 10℃ / min. In order to improve the accuracy of the test, three tests are performed for each group.

4. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: Before the wettability test, first, the copper substrate was cleaned with alcohol in an ultrasonic cleaner for two minutes; then, 0.2±0.01 g of the sample was coated on the copper substrate and heated on a constant temperature hot plate for 30 minutes at a heating temperature of 250°C; after cooling to room temperature, the sample was removed from the constant temperature hot plate; after the sample was cooled, it was photographed with a camera, and the spreading area of ​​the solder was measured using ImageJ software; finally, the average spreading area of ​​the composite solder of the same composition was calculated.

5. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: Before the shear test, a Cu plate with a length of 40 mm, a width of 4 mm and a height of 0.6 mm was manually polished using sandpaper of different particle sizes; then it was immersed in alcohol and ultrasonically cleaned; then the solder and the Cu plate were prepared into samples required for the shear test; finally, the shear test was performed using an electronic universal testing machine of model UTM5000.

6. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.05%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

7. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.1%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

8. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.2%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

9. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.4%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.

10. The Sn-based solder capable of realizing high-reliability interconnection of microwave components according to claim 1, characterized in that: The Sn-based solder composition and the mass percentage of each component are preferably: Cu NWs content is 0.8%, Cu content is 0.5%, Ag content is 1.0%, and the rest is Sn.